Differential proteome analysis of the leaves of lead hyperaccumulator, Rhoeo discolor (L. Her.) Hance. (27th November 2020) - Enot, Melania M.; Weiland, Florian; Mittal, Parul; Hoffmann, Peter; Sillero‐Mahinay, Myrna; Pukala, Tara
Abstract: The present study investigated Rhoeo discolor (L. Her.) Hance for its ability to accumulate Pb, which is of relevance to phytoremediation applications. Based on this analysis, plants were found to accumulate greater than 10 mg/g (0.1%) of dry weight Pb in the shoots, which classifies the plant a Pb hyperaccumulator. Further, changes in the leaf proteome profiles in response to Pb stress were investigated. Wild‐type plants were subjected to a high concentration of Pb(NO3 )2, and the levels of Pb that accumulated in different plant tissues were determined using atomic absorption spectrophotometry. Using 2D‐difference gel electrophoresis, 181 protein spots were detected to be differentially abundant in response to Pb stress and selected spots exhibiting the strongest differential abundance suggested an impairment of the photosynthetic apparatus of the plant under Pb stress. Subsequently, a more extensive, proteome wide analysis utilizing label‐free quantitation further identified a predominant decrease in protein levels and a significant effect on the nuclear proteome, as well as photosynthesis, carbon fixation and metabolism, providing insight into the Pb tolerance of this system in a potential phytoremediation context.